The Pānānā or "Sighting Wall" at Hanamauloa, Kahikinui, Maui: Archaeological Investigation of a Possible Navigational Monument - Kirch, Patrick V.; Ruggles, Clive; Sharp, Warren D. (Waka Kuaka, 2013)
A unique stone monument consisting of a notched, linear wall and associated features, situated at Hanamauloa in Kahikinui District, Maui Island, is interpreted as a probable pre-contact navigational structure. Ethnographic testimony refers to the structure as a pānānā or "sighting wall". Archaeological investigation revealed that the wall and associated cairn and upright are positioned so that the notch precisely frames the stars of the Southern Cross when the constellation is exactly positioned above the upright slab visible through the notch. In Hawaiian traditions, the Southern Cross is known as a guiding star to Kahiki, the ancestral homeland. Precise Uranium-series dating of branch coral associated with the cairn suggests an age of AD 1444 ± 4 for 68 construction and/or use of the site. The broader geographical context of the monument is also discussed, including a suite of place names referring to ancestral Polynesian lands. Finally, it is suggested that the pānānā may relate to an important figure in Hawaiian oral traditions, the voyaging chief La'amaikahiki.